The Relationship Between the Intensity of Using Instagram and Learning Motivation for Students at Muhammadiyah University of Sidoarjo - Mochamad Syahrial Mubarak; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to see whether there is a relationship between the intensity of Instagram use and student motivation. The data collection method in this research uses correlational quantitative methods. The variables of this research are the intensity of the use of Instagram as an independent variable and learning motivation as the dependent variable. The population of this research is all even semester students of the 2019/2020 academic year at Muhammadiyah University of Sidoarjo, totaling 10,182 students. The sample used for the study amounted to 347 subjects using random sampling technique. Data collection techniques in this study used a psychological scale of learning motivation and an intensity scale with a Likert scale model. There is a negative relationship between the intensity of using Instagram and learning motivation for students at the Muhammadiyah University of Sidoarjo. The correlation coefficient value is 0.361 with a significance of 0.000 < from 0.05. Then based on the test results the coefficient of determination shows 0.183 which indicates that the intensity of the use of Instagram provides an effective contribution to learning motivation and the rest is influenced by other variables.